High prevalence of myopia in children and their parents in Hong Kong Chinese Population: the Hong Kong Children Eye Study. Issue 5 (24th January 2020) - Yam, Jason C.; Tang, Shu Min; Kam, Ka Wai; Chen, Li Jia; Yu, Marco; Law, Antony K.; Yip, Benjamin H.; Wang, Yu Meng; Cheung, Carol Y. L.; Ng, Danny S.C.; Young, Alvin L.; Tham, Clement C.; et al.
Abstract: Purpose: To determine the myopia prevalence in Hong Kong Chinese children and their parents. Methods: It was a population‐based cross‐sectional study. A total of 4257 children aged 6–8 years, and 5880 parents were recruited in the Hong Kong Children Eye Study. Cycloplegic autorefraction was measured for children; and non‐cycloplegic autorefraction for parents. Parental educational level, children's outdoor time, and near work were collected by validated questionnaires. Results: In children aged 6–8 years, 25.0% were myopic, and among them, 12.7% for the 6‐year‐olds, 24.4% for the 7‐year‐olds and 36.1% for the 8‐year‐old. About 0.7% of children aged 8 years were high myopia. In all age groups, boys (their myopia rate: 13.9% at 6 years, 26.7% at 7 years, and 38.3% at 8 years) were more myopic than girls (11.3% at 6 years, 22.0% at 7 years, 33.4% at 8 years). Among parents, 72.2% were myopic (mother, 73.2%; father, 70.7%) and 13.5% high myopia (mother, 12.8%; father, 14.5%). It was observed that prevalence decreased with ages and increased with education level. Conclusion: There is a strikingly high prevalence of myopia in Hong Kong children aged 6–8, much higher than that of other regions of China. Of note, the prevalence of children was similar to that in 15 years ago. Furthermore, the myopia prevalence of parents is high, and it had already increased in this cohort. Prevention of childhood myopia is important, likewise for visual complications from high myopia in adults.